6x+8=8-12x+6

Simple and best practice solution for 6x+8=8-12x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+8=8-12x+6 equation:


Simplifying
6x + 8 = 8 + -12x + 6

Reorder the terms:
8 + 6x = 8 + -12x + 6

Reorder the terms:
8 + 6x = 8 + 6 + -12x

Combine like terms: 8 + 6 = 14
8 + 6x = 14 + -12x

Solving
8 + 6x = 14 + -12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12x' to each side of the equation.
8 + 6x + 12x = 14 + -12x + 12x

Combine like terms: 6x + 12x = 18x
8 + 18x = 14 + -12x + 12x

Combine like terms: -12x + 12x = 0
8 + 18x = 14 + 0
8 + 18x = 14

Add '-8' to each side of the equation.
8 + -8 + 18x = 14 + -8

Combine like terms: 8 + -8 = 0
0 + 18x = 14 + -8
18x = 14 + -8

Combine like terms: 14 + -8 = 6
18x = 6

Divide each side by '18'.
x = 0.3333333333

Simplifying
x = 0.3333333333

See similar equations:

| 2b-9=3 | | 7a*7a+32=7-40a | | -7725+185x=0 | | -7725+185x=-12790 | | 9x^2+14=-50 | | z/10=8=4 | | x=18-4 | | 7x+80=12x | | 0.4=(400-x)/x | | -6x*1/9=-18 | | -6x*1/9=-19 | | 9x+4=45 | | -6x1/9=-18 | | cos(1.57)=0 | | 0.20(x+23)+0.50(x)=26.30 | | 10+2y=6y+6 | | 0.35=(20-x)/20 | | kx^2-(2k-2)x+4=0 | | 7x^3-9x+6=0 | | Cos^2(x)-5cos(x)+4=0 | | -11x-6= | | 3p(q-6)= | | 0.20(x+23)+0.50(y)=26.30 | | 7x^3-9x-6=0 | | 3p(a-6)= | | 100-6x=3x+10 | | x-142=42 | | 9p+2t-4p+5t= | | e=3f/-5f | | 3e*3f= | | 32+-5x=8+3x | | -7x+3y=8x-10 |

Equations solver categories